2005
DOI: 10.1128/jb.187.1.213-223.2005
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit Complementation of Sugar Signal Transduction in VirA Heterodimers and Posttranslational Regulation of VirA Activity inAgrobacterium tumefaciens

Abstract: The VirA/VirG two-component regulatory system of Agrobacterium tumefaciens regulates expression of the virulence (vir) genes that control the infection process leading to crown gall tumor disease on susceptible plants. VirA, a membrane-bound homodimer, initiates vir gene induction by communicating the presence of molecular signals found at the site of a plant wound through phosphorylation of VirG. Inducing signals include phenols, monosaccharides, and acidic pH. While sugars are not essential for gene inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…In contrast, complete removal of medium components from the inoculation medium, i.e., only D. W., gave significantly lower transformation efficiency (6.7%), suggesting the importance of maltose during infection period for the successful transformation with Agrobacterium. Previous studies demonstrated that sugars greatly increased the expression of vir genes in combination with AS (Shimoda et al 1990;Wise et al 2005). In the present study, difference in the presence of maltose in medium was made only at short period of inoculation but not at subsequent cocultivation period.…”
Section: Effect Of Different Stage Of Plbs After Subculture and Inocusupporting
confidence: 48%
“…In contrast, complete removal of medium components from the inoculation medium, i.e., only D. W., gave significantly lower transformation efficiency (6.7%), suggesting the importance of maltose during infection period for the successful transformation with Agrobacterium. Previous studies demonstrated that sugars greatly increased the expression of vir genes in combination with AS (Shimoda et al 1990;Wise et al 2005). In the present study, difference in the presence of maltose in medium was made only at short period of inoculation but not at subsequent cocultivation period.…”
Section: Effect Of Different Stage Of Plbs After Subculture and Inocusupporting
confidence: 48%
“…The presence of biologically relevant dimers has been demonstrated both biophysically and genetically for the Tar chemoreceptor and histidine kinases such as PhoQ, DcuS, NarX, and TorS (20,32,77,79). The evidence for VirA dimers comes by way of genetic analysis using intersubunit complementation (9,66,73) and by chemical cross-linking analysis indicating that VirA exists as a dimer even in the absence of the inducing ligands (57). While these earlier studies affirm that VirA exists as a dimer and that dimerization is critical to VirA function, our investigations demonstrate periplasmic domain dimerization in the absence of tethering via transmembrane and cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 99%
“…pAW10 and pYW47 are similar in that they are both derivatives of pYW10 (31,37). Derivatives of these plasmids are expected to be present in Agrobacterium at levels between 15 and 20 copies per pTi (37). Plasmid pAW168 was constructed by first moving the 7-kb HpaI insert from pVRA6 to pAW24.…”
Section: Methodsmentioning
confidence: 99%